Determining an additional diagnostic parameter for improving the accuracy of assessment of the condition of stator windings in an induction motor - Gubarevych, Oleg; Goolak, Sergey; Daki, Olena; Yakusevych, Yuriy (Eastern-European Journal of Enterprise Technologies, 2021)
This paper has proposed and substantiated the application of an additional diagnostic parameter for assessing the state of stator windings of induction motors during operation. The dependences of the values of phase shifts between phase currents and phase voltages have been obtained. These dependences showed that when an inter-turn short circuit occurs in the stator windings, the phase shifts are the same for all phases of the motor. That has made it possible to obtain the dependence of the change in phase shift on the change in the engine shaft rotation frequency. This study’s result has established the dependence of the rates of change of the phase angle on the engine shaft rotation frequency for both one and two damaged phases with varying degrees of damage. When analyzing these dependences, it was found that with an increase in the number of damaged phases of the electric motor, the linear section of the dependences decreases. In addition, with an increase in the degree of phase damage, the angle of inclination of the linear sections of the characteristics decreases. That has made it possible to determine an additional parameter for diagnosing the place and degree of an inter-turn short circuit of the windings in an induction motor with a squirrel-cage rotor. The values of the additional parameter, termed by this paper’s authors as a "phase criterion" can be used to assess the condition and degree of damage to the stator winding of induction motors. The values of the phase criteria for various types of damage were: when phase A is damaged by 90 %, ξ=0.634, (deg)2/(rpm)2; when phase A is damaged by 80 %, ξ=0.393, (deg)2/(rpm)2; when phase A is damaged by 80 % and phase B is damaged by 90 %, ξ=0.25, (deg)2/(rpm)2; when phase A is damaged by 80 % and phase B is damaged by 90 %, ξ=0.173, (deg)2/(rpm)2. The results of this research could be used to select an effective method for diagnosing an inter-turn short circuit in the stator winding when building a diagnostic system for induction motors as part of drives of transport equipment